Cryopreserved Umbilical Cord Mesenchymal Stem Cells Show Comparable Effects to Un-Cryopreserved Cells in Treating Osteoarthritis - Bo Yan; Huixin Chen; Li Yan; Qiang Yuan; Le Guo (Cell Transplantation)
Non-cryo and hypothermic preservations are two available options for short-term storage of living cells. For long-term cell storage, cryopreservation is an essential procedure as it prolongs the storage time, allowing for the transport and testing of cells, as well as the establishment of cell banks. But it is unclear whether cryopreservation reduces the therapeutic effects of human umbilical cord mesenchymal stem cells (hucMSCs) on osteoarthritis (OA). To investigate this, we compared the basic biological characteristics and the anti-OA efficacy of un-cryopreserved hucMSCs (UC-MSCs) and cryopreserved hucMSCs (C-MSCs). A mono-iodoacetate-induced rat OA model was established to evaluate the anti-OA properties of UC-MSCs and C-MSCs. And the conditioned medium of UC-MSCs (UC-CM) and cell freezing medium of C-MSCs (C-CFM) were collected for the mechanism study. No significant differences were found between UC-MSCs and C-MSCs in cell viability, immunophenotype, and trilineage differentiation capacity. In vivo, UC-MSCs and C-MSCs exhibited similar cartilage-repairing effects by attenuating pain and alleviating pathological changes in OA rat joints. In vitro, C-CFM and UC-CM promoted the proliferation of chondrocytes, improved the expression of anabolism-related molecules ( Col2 , COL2, and SOX9), and decreased the expression of catabolism-related molecules ( Adamts5 , Mmp13 , Il6 , COL10, and MMP13). These results indicated that UC-MSCs and C-MSCs had comparable anti-OA effects, and cryopreservation did not alter the anti-OA capability of hucMSCs, which provides further support for clinical use of C-MSCs in treating OA.